2021
DOI: 10.21062/mft.2021.074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Porosity of Aluminum Alloys Castings Produced by Squeeze Casting

Abstract: The results of researches on porosity and structure of castings from AlMg9, AlSi7Mg and AlCu4Ti alloys produced by squeeze casting and for comparison by gravity die casting are presented. The tests were carried out on 200x100x25mm plates squeeze casted under 90MPa pressure. Prior to the commencement of experimental studies, numerical simulations of solidification were made for the selected alloy (AlSi7Mg) in order to determine the potential locations of shrinkage porosity. As part of the study, the porosity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Once the cavity is full, a pressure is added to the melt to over 100 MPa and held to compensate for shrinkage until the casting has solidified [10]. Zyska and Boro ń [14] compared the porosity of three aluminium castings, AlMg9, AlSi7Mg, and AlCu4Ti, made by gravity die casting and squeeze casting. The results showed that the porosity in the castings made by squeeze casting was almost half that of the castings made by gravity die casting.…”
Section: Aluminium Casting Processesmentioning
confidence: 99%
“…Once the cavity is full, a pressure is added to the melt to over 100 MPa and held to compensate for shrinkage until the casting has solidified [10]. Zyska and Boro ń [14] compared the porosity of three aluminium castings, AlMg9, AlSi7Mg, and AlCu4Ti, made by gravity die casting and squeeze casting. The results showed that the porosity in the castings made by squeeze casting was almost half that of the castings made by gravity die casting.…”
Section: Aluminium Casting Processesmentioning
confidence: 99%